Novel Mutation of Interferon-γ Receptor 1 Gene Presenting as Early Life Mycobacterial Bronchial Disease. (November 2016) - Gutierrez, Maria J.; Kalra, Neelu; Horwitz, Alexandra; Nino, Gustavo
Mendelian susceptibility to mycobacterial diseases (MSMD) are a spectrum of inherited disorders characterized by localized or disseminated infections caused by atypical mycobacteria. Interferon-γ receptor 1 (IFNGR1) deficiency was the first identified genetic disorder recognized as MSMD. Mutations in the genes encoding IFNGR1 can be recessive or dominant and cause complete or partial receptor deficiency. We present the case of a 2½-year-old boy with a history of recurrent wheezing, diagnosed with endobronchial mycobacterial infection. Immunological workup revealed a homozygous nonsense mutation in the IFNGR1 gene, a novel mutation predicted in silico to cause complete IFNGR1 deficiency. This case demonstrates that ( a ) Interferon-γ receptor deficiency can present resembling common disorders of the lung; ( b ) mycobacterial infections should be suspected when parenchymal lung disease, hilar lymphadenopathy, and endobronchial disease are present; and ( c ) high index of suspicion for immunodeficiency should be maintained in patients with disseminated nontubercular mycobacterial infection.